Geometria métrica e topologia de superfícies algebricamente parametrizadas - Pereira, Rodrigo Mendes (2016)
In this work, we study the singularities of the surfaces obtained as an image of a plane by an algebraic or analytic application in the spaces R3 and R4. We study the topological and metric properties of the knots that are obtained as a link of this surfaces. Normal embedding criterion are obtained for the surfaces and, in addition, the connections between the topology of the knot and normal embedding are investigated. We will also give a description of the tangent cones of these surfaces at the singular points.